ANALISIS PENGARUH SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE BLACKBERRY PADA MAHASISWA MANAJEMEN EKSTENSI FAKULTAS EKONOMI USU - vivi maisyarah (Jurnal Media Informasi Manajemen, 2013)
Consumer attitudes is the tendency of consumers to evaluate brands either liked or disliked by the consumer consistently. This study used questionnaires, in order to identify and analyze the effect of consumers' attitude toward product purchasing decisions on a BlackBerry phone extension management USU students. This study uses descriptive analysis. The population used in this study were students of the Faculty of Economics USU Extension Management using BlackBerry Mobile. With a sample as many as 65 students. The data was processed using simple linear regression analysis, determinasi coefficient and t-test. The results showed that the attitudes of consumers who use mobile phones BlackBerry has a positive and significant impact on consumer purchasing decisions at the Faculty of Economics, Management Students USU Extension. Value of coefficient of determination equal to 0.502 means the ability of variable consumer attitudes on BlackBerry mobile products in explaining the purchasing decisions at Management Students of the Faculty of Economics USU Extension by 50.20% and the remaining 49.80% influenced by other variables that are not included in this study. Keywords: Consumer Attitudes and Purchase Decision.